Animal Abuse among High-Risk Youth: A Test of Agnew's Theory. Issue 6 (2nd June 2020) - Mowen, Thomas J.; Boman IV, John H.
ABSTRACT: Concern over animal abuse among policy-makers, law enforcement officials, and the general public remains high. Although research has marked animal abuse as an indicator of a variety of deviant outcomes, fewer projects have examined the correlates of cruelty towards animals. In this study, we apply Agnew's theory of animal abuse to explore how a wide-range of characteristics relate to deviance towards animals. In support of Agnew's theory, results reveal that a combination of individual traits and behaviors, socialization experiences, and mechanisms of social control significantly relate to animal abuse. However, measures of strain do not appear to relate to animal abuse, providing only partial support to the theory.